The Economical Analysis Of Mechanization In Land Preparation For Plantation - M.C. Tri Atmodjo (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
One of the development of technology in agricultural engineering  is the farm mechanization by using farm tractor equipped with disc plow and ridger for land preparation of the plantation. The choose of agrticultural machinery should consider the technical and economical value and the culture of the farmer themselves.     The economical analysis shows that One tractor 70 HP and the new price about   800 million rupiah  should cultivate 1007hectars of land for a year which 5 years operation until obsolete.  The true analysis of technical and economical in the application of   farm machinery   would   increase  the total revenue and benefit of plantation.